Is Redshirting Beneficial for Reading Acquisition Success? - Sucena, Ana; Marques, Cátia; Silva, Ana Filipa; Garrido, Cristina; Pimenta, Rui (Frontiers in Psychology, 2020)
The controversy around the effect of academic redshirting on reading acquisition continues receiving attention in the international literature. However, few studies are known with non-English speaking children. In this study we intend to understand this phenomenon with 698 Portuguese speaking first graders, 360 girls (51.6%), aged between 5 years old and 8 months and 7 years old and 6 months (M = 6.3 months, SD = 3.9 months). Reading acquisition precursors were assessed namely phonemic awareness and letter-sound knowledge. Results reveal that 5.9% of first graders are redshirted. Clusters analysis indicated two clusters per variable. Cluster 1 with low phonemic awareness and letter-sound knowledge and low socioeconomic status, cluster 2 with high phonemic awareness and letter-sound knowledge and medium-high socioeconomic status. The cluster results suggest a prevalence of 24.5% children at risk of having learning difficulties. The MANOVA indicated that only socioeconomic status has an effect on phonemic awareness and letter-sound knowledge, with children from medium-high level presenting higher results. It is concluded that redshirting did not bring additional advantages for reading acquisition success. Implications about the importance of education in order to lessen those differences, as well as prevent difficulties are presented.